When you divide a variable with an exponent by a variable with an exponent, you subtract the exponents (only if the bases/variables are the same)
For example:
[tex]\frac{x^2}{y^2}[/tex] Since they have different variables (x and y), you can't simplify this anymore
[tex]\frac{x^5}{x^3} = x^{5-3}=x^2[/tex]
[tex]\frac{z^3x^7}{z^2yx^2} = (\frac{1}{y})(z^{3-2})(x^{7-2}) = (\frac{1}{y} )(z^1)(x^5) = \frac{zx^5}{y}[/tex]
( if the exponent happens to come out negative, you have to move the variable and the exponent to the other side of the fraction to make the exponent positive)
Ex:
[tex]\frac{x^2}{x^4} =x^{2-4}=x^{-2} = \frac{1}{x^2}[/tex]
[tex]\frac{-44a^3b^4-64a^4b^3-84ab}{-4ab}[/tex] SInce they all have a common factor of 4, you can divide out -4
[tex]\frac{11a^3b^4+16a^4b^3+21ab}{ab}[/tex]
If you follow the steps from ^^^^^^^, you should get
[tex]11a^2b^3+16a^3b^2+21[/tex]